Diagnostic Methods for Histoplasmosis: Focus on Endemic Countries with Variable Infrastructure Levels (2014)
Diagnosis of histoplasmosis remains challenging in resource-limited regions where HIV/AIDS is epidemic and histoplasmosis is endemic. Early and rapid detection of histoplasmosis is essential to preventing morbidity and mortality, yet few diagnostic options are available in low-resource areas of the world. The aim of this review is to provide an overview of the current status of the diagnosis of histoplasmosis, including an update on recent developments and utilization of new technologies. We discuss the specific diagnostic challenges faced in endemic regions, emphasizing the need for greater availability and standardization of rapid diagnostics for this endemic and neglected disease. While significant progress has been made in the development of new methods, clinical utility must be established by means of formal and extensive clinical studies. © 2014, Springer International Publishing AG (outside the USA).